Methodical Approach to the Formation of the Forecast Labor Intensity of the Development (Modernization) of Complex Technical Systems - Alexander G. Podolsky; Alexey V. Babkin (Учёт. Анализ. Аудит)
Subject. The subject of the research are methodological aspects of formation of the forecast of the complexity of creation (modernization) of complex technical systems. Purpose. The purpose of this article is to increase the efficiency use of human and financial resources for the development (modernization) of complex technical systems. Methodology. The lack of methodological support of the formation of the complexity of developmental works on creation of complex technical systems has led to the development of the approach to its study. His presentation is based on the system analysis and decomposition methods of complex technical systems and synthesis of their constituent parts at different levels of decomposition. The development process is considered as a set of stages, each of which has its own specific features and requires workers with different specialization. To reflect the volume of work associated with development, complex technical system is decomposed into subsystems and components, and stages of development - the tasks and subtasks that must be solved in their implementation. In order to provide a rational decomposition of the formed requirements it must satisfy. Results. The developed technique of an estimation of complexity of development (modernization) of complex technical systems, allowing to obtain a predictive evaluation of the implementation of the most important stages of development: the development of sketch and technical projects; development of design documentation for manufacturing a prototype; prototyping; performance of state tests of the prototype; the approval of working design documentation for industrial (serial) production. Conclusions. The proposed methodical approach can serve as a basis for the development of interdepartmental methodological recommendations for assessing the complexity of creating (upgrading) complex technical systems.